Features of the system of antioxidant protection and lipid peroxidation in microangiopathies against type 2 diabetes mellitus - Savitsky, I.; Gritsan, I.; Sarakhan, V.; Sirman, Ya.; Preys, N. (Journal of Education, Health and Sport, 2020)
The article presents the results of an experimental study of the AOР and LPО system in animals simulated complications of the microcirculatory tract (diabetic retinopathy, diabetic nephropathy) on the background of type 2 diabetes. It was found that in the group of animals with type 2 diabetes increased the level of DC, TBCproducts and MDA; catalase and FG levels decreased. In animals with simulated DN, AOP disorders were more pronounced compared to animals with DR. This trend can be explained by the fact that in addition to hyperglycemia in these animals, the excessive formation of free radicals contributes to metabolic shifts in ischemic areas of tissues and organs. Disturbance of balance in AOP and LPO in type 2 diabetes triggers a pathogenetic cascade of development of complications of the microcirculatory tract and is accompanied by a tendency to further increase the generation of reactive oxygen species and activation of POL in microangiopathies.